Drying kinetics mathematical modeling of coffee (Coffea arabica L.) processed in different ways and with the use of enzymes and yeast (Research, Society and Development, 2020)
Among all stages in the coffee production (Coffea arabica L.), post-harvest can significantly impact the final cost and product quality. Among the stages of this phase, drying is one’s that requires most care. The search for new technologies to optimize this process has been growing exponentially, a example is the use of enzymes and yeasts, which can guarantee a safer drying and even improve the quality of the bevarege. The objective of the study was to evaluate the drying behavior of coffee without changing the temperature, air flow, only changing the processing (natural and pulped natural) of the beans using the enzyme Pectinex® Ultra SPL and the yeast CA11 to observe the occurrence of some change in the drying kinetics after processing and modeling the drying kinetics, analyzing which model can more accurately predict the coffee drying. The VALCAM model was the best model to describe drying kinetics, with the highest value of determination coefficient (R2> 99.73%), lowest mean relative deviation value (P